Risk factors associated with degenerative glenohumeral osteoarthritis - Ravi Prakash; Nitin B Jain; Ziyi Chen; Folefac D Atem; Michael S Khazzam; Rashmi Pathak; Daniel Tai; Ursa BezanPetric; Estefanie Garduno Rapp (BMJ Open Sport & Exercise Medicine)
Objective Glenohumeral (GH) osteoarthritis (OA) is the third most common large joint disease, after hip and knee OA. This study aimed to identify risk factors for GH OA.Methods We used data from the Dallas Shoulder cohort, including individuals aged 40–85. Those with confirmed GH OA based on X-ray were cases, and those without were controls. Univariate, least absolute shrinkage and selection operator and multivariate analyses identified risk factors, including age, body mass index (BMI), sex, work-related shoulder problems, shoulder disability, dislocation, previous trauma, surgery, smoking, hypertension, diabetes, depression, heart disease, OA, night pain and overall sleep quality.Results A total of 1827 cases and 1556 controls were identified for GH OA. In univariate analysis, significant associations with GH OA were found for increasing age (>40 to ≤50: OR 3.29, 95% CI 2.44 to 4.45; >50 to ≤60: OR 5.90, 95% CI 4.49 to 7.77; >60 to ≤70: OR 12.18, 95% CI 9.22 to 16.08 and >70: OR 16.54, 95% CI 12.47 to 21.94), higher BMI (≤19: OR 1.44, 95% CI 1.01 to 2.04; >25 to ≤30: OR 1.57, 95% CI 1.32 to 1.86; >30 to ≤35: OR 1.85, 95% CI 1.54 to 2.22 and >35: OR 1.77, 95% CI 1.28 to 2.45), prior shoulder injury (OR 1.30; 95% CI 1.12 to 1.50), shoulder surgery history (OR 0.71; 95% CI 0.57 to 0.87), shoulder pain at night (OR 1.35; 95% CI 1.07 to 1.70) and hypertension (OR 0.70; 95% CI 0.60 to 0.81). In multivariate analysis, significant associations remained for age (>40 to ≤50: OR 2.99, 95% CI 2.21 to 4.06; >50 to ≤60: OR 5.48, 95% CI 4.14 to 7.23; >60 to ≤70: OR 11.22, 95% CI 8.44 to 14.88 and >70: OR 16.65, 95% CI 12.45 to 22.17), BMI (≤19: OR 1.49, 95% CI 1.01 to 2.20; >25 to ≤30: OR 1.45, 95% CI 1.20 to 1.77; >30 to ≤35: OR 1.70, 95% CI 1.39 to 2.09 and >35: OR 1.78, 95% CI 1.25 to 2.55) and previous shoulder trauma (OR 0.80; 95% CI 0.68 to 0.94).Conclusion We identified increasing age and higher BMI as factors associated with GH OA. Due to the large sample size, many risk factors were assessed. Since the shoulder is not a weight-bearing joint, the BMI-GH OA link is likely molecular and systemic, warranting further investigation.Level of evidence Prognostic level III.